The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1086/427712
|View full text |Cite
|
Sign up to set email alerts
|

Active and Star-forming Galaxies and Their Supernovae

Abstract: To investigate the extent to which nuclear starbursts or other nuclear activity may be connected with enhanced star formation activity in the host galaxy, we perform a statistical investigation of supernovae (SNe) discovered in host galaxies from four samples: the Markarian galaxies sample, the Second Byurakan Survey (SBS) sample, the north Galactic pole ( NGP) sample of active or star-forming galaxies, and the NGP sample of normal galaxies. Forty-seven SNe in 41 Mrk galaxies, 10 SNe in six SBS galaxies, 29 SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 61 publications
7
47
0
Order By: Relevance
“…6, as well as Table 5). This result has been known for some time (e.g., van den Bergh 1997; Wang et al 1997;Petrosian et al 2005;Hakobyan 2008) for the distribution of radii normalized to R 25 , but we confirm the more centrally concentrated distribution of SNe Ib/c with our normalization to the disk scale lengths (Fig. 6 and Table 5).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…6, as well as Table 5). This result has been known for some time (e.g., van den Bergh 1997; Wang et al 1997;Petrosian et al 2005;Hakobyan 2008) for the distribution of radii normalized to R 25 , but we confirm the more centrally concentrated distribution of SNe Ib/c with our normalization to the disk scale lengths (Fig. 6 and Table 5).…”
Section: Discussionsupporting
confidence: 87%
“…Petrosian & Turatto (1990) found that their sample of 8 SNe II and SNe Ib within galaxies hosting AGN were significantly more radially concentrated in their galaxy hosts than analogous CCSNe in galaxies without active nuclei. Petrosian et al (2005) studying a sample of 12 SNe II and SNe Ib/c in galaxies hosting AGN, confirmed this result and found that SNe Ib/c in active/star-forming galaxies are more centrally concentrated than are the SNe II, but given the small sample, this difference was not statistically significant. These results were confirmed with larger samples of CCSNe by Hakobyan (2008), who used both one-dimensional and multivariate statistics.…”
Section: Introductionmentioning
confidence: 78%
“…For example, Wang et al (2010) directly measured number and surface density distributions of SNe II in their hosts, and indicated that SNe II detected in star-forming galaxies follow an exponential law, in contrast, the distribution of SNe II detected in Active Galactic Nuclei (AGN) hosts significantly deviates from an exponential law. Petrosian et al (2005) studying a sample of CC SNe in galaxies hosting AGN found that SNe Ibc in active/star-forming galaxies are more centrally concentrated than are the SNe II, but given the small sample, this difference was not statistically significant. The results of Petrosian et al were confirmed with larger samples of CC SNe by Hakobyan (2008).…”
Section: Introductionmentioning
confidence: 96%
“…However, other authors have shown that the SNe distributions in galaxies with various activity levels might be different (e.g., Petrosian & Turatto 1990;Petrosian et al 2005;Hakobyan 2008;Wang et al 2010;Herrero-Illana et al 2012). For example, Wang et al (2010) directly measured number and surface density distributions of SNe II in their hosts, and indicated that SNe II detected in star-forming galaxies follow an exponential law, in contrast, the distribution of SNe II detected in Active Galactic Nuclei (AGN) hosts significantly deviates from an exponential law.…”
Section: Introductionmentioning
confidence: 98%
“…They also found that the ratio N Ibc /NII measured in Sy galaxies exceeds that in normal host galaxies by a factor of 4. Studying a sample of CC SNe in galaxies hosting AGN, Petrosian et al (2005) and Hakobyan (2008) found that the SNe in active/star-forming (SF) galaxies are more centrally concentrated than those in normal galaxies. Herrero-Illana, Pérez-Torres & Alberdi (2012) modelled the radial distribution of SNe in the nuclear starbursts of M 82, Arp 220, and Arp 299A galaxies, and interpreted the results as evidence of galaxy-galaxy interactions that are expected to trigger massive star formation down to the central kiloparsec region of galaxies.…”
Section: Introductionmentioning
confidence: 99%